O comércio eletrônico e os impactos da PEC 197/2012 na arrecadação de ICMS do Paraná - Cieslak, Paulo Henrique (2014)
The emergence of e-commerce as a result of technological developments changed various scenarios, including the tax. The present study, using bibliographical research, sought to clarify the reasons for the controversy created between the States of the Federation, regarding the allocation of tax revenues the ICMS generated by this type of business, which resulted in the proposal of amendment to the Constitution n° 1972012. Then, through documentary research in the State of Paraná, revenue sought to estimate the financial impact in the State, if there is approval of the legislative amendment proposed. The results indicated a balance between purchases and sales, consequently no major impacts in the storeroom of the ICMS. Such a conclusion, however, is not final, since the disposal of part of the data of the survey, in the face of detected inconsistencies and difficulties in classification of various operations, whether or not in-person face-to-face. However, the topics covered have identified some details that require more reflection on the part of tax administrations, aimed at efficient control and deployment of the proposed amendments.